Estimating the incidence of dengue in international air travelers from non-endemic countries between 2010-2019. - Matt D T Hitchings; Yi Xu; Bernardo García-Carreras; Adriana Gallagher; Justin J O'Hagan; Derek A T Cummings (PLoS Neglected Tropical Diseases)
Background There have been increasing numbers of travel-associated dengue cases reported but the true burden is unclear. Existing surveillance in non-endemic countries captures only a fraction of symptomatic cases in returning travelers due to underreporting. Therefore, we used mathematical modeling approaches to account for underreporting and estimate the number of dengue cases occurring during international travel. Methodology/principal findings We obtained data on numbers of international air passengers from 43 non-endemic "origin" countries, risks of infection while in 119 dengue-endemic locations ("destinations"), and average durations of stay. We estimated travel-associated infections by multiplying the time spent by travelers in endemic countries by the risk of dengue infection and used data on reported cases to infer the fraction of cases that are included in surveillance systems. Our model estimated there were an average of 64,623 (95% CI: 25,068-138,283) symptomatic dengue cases ("cases") and 303,870 (95% CI: 292,841-315,240) total dengue infections (i.e., including symptomatic and asymptomatic infections) across 43 origin countries annually between 2010-19. The USA had the highest number of estimated cases followed by China. Among 34 origin countries that reported dengue cases, the fraction of cases reported varied widely (median 24.9%, range 2.5%-100%). The destination countries where most cases were infected were India, followed by Thailand. Conclusions/significance We estimated a substantial burden of dengue among international air travelers from 43 non-endemic origin countries. The fraction of cases reported varied widely across origin countries and was also influenced by the specific origin-destination country pair examined.